Deterministic and scalable generation of exciton emitters in 2D semiconductor nanodisks - Feng, Shun (2022)
In recent cryogenic measurements, narrow photoluminescence (PL) peaks due to diverse quantum emitters have been found at random locations of monolayer transition metal dichalcogenides (TMDs), which impedes precise optoelectronic applications. Thus, it is of great importance to truly regulate these localized exciton emissions by deterministic spatial and spectral control. Here, such desired emission is primarily demonstrated in monolayer WS2 nanodisks. The size-dependent PL studies indicate the clear evolution from the broad defect-band emission to a set of spectrally isolated narrow peaks (linewidth of ≈ sub nm) at 4.2 K, which is associated with the prevailing effect of edge defects with the shrinkage of the disk diameter, providing a narrow emission energy range for bound excitons. When the disk diameter is reduced to 300 nm, more than 80% of emitter peaks are located between 610 and 616 nm, verifying the effective control of emission wavelength of these photon emitters. Furthermore, the strategy is extended to prepare scalable WS2 nanodisk arrays based on flakes of hundreds of µm, and size-dependent narrow emissions of WSe2 nanodisks are testified. This work develops a defect-engineering strategy to generate localized exciton emitters toward the promising TMD-based optoelectronic applications.